(untitled) (NTU journal for Administrative and Human Sciences (JAHS), 2025)
The current research sought to study the role of technical creativity as an independent variable in promoting innovative marketing as a dependent variable in the research sample represented by managers at the General Company for Communications Equipment and Power/Al-Kindi Factory. the research intellectual and field research problem was embodied by asking a research question: Is there a correlation and a moral impact of the dimensions of technical creativity in innovative marketing? the two researchers crystallizing the conceptual framework and adopted the descriptive analytical approach whcih relying on a set of tools for collecting data and information represented by a questionnaire form and field visits in In addition to personal interviews, also the two researchers developed a hypothetical plan to see how the result obtained can devioted from natural value which It reflects the nature of the relationships of correlation and influence between technical innovation, which includes its four dimensions (introducing a new product, improving an existing product, designing a new production process, improving an existing production process) and innovative marketing (assigning resources, developing marketing technology, attracting the customer, and calculated risks).the result of main htpothesiss and many sub-hypotheses was tested at Al Kindi Factory through the use of the ready-made statistical program (SPSS v.23).The research reached a set of results, the most important of which is the existence of a significant correlation between technical creativity and innovative marketing and a significant correlation of technical creativity and innovative marketing in the investigated organization.